The feasibility and importance of adding measures of actual experience to cross-sectional data collection - Francine D. Blau; Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2011)
We use Michigan Panel Study of Income Dynamics data and data from a 2008 telephone survey of adults conducted by Westat for the Princeton Data Improvement Initiative (PDII) to explore the importance and feasibility of adding retrospective questions about actual work experience to cross-sectional data sets. We demonstrate that having such actual experience data is important for analyzing women's post-school human capital accumulation, residual wage inequality, and the gender pay gap. Further, our PDII survey results show that it is feasible to collect actual experience data in cross-sectional telephone surveys like the March Current Population Survey annual supplement.
urn:nbn:de:101:1-201108093008
Keywords: C81; J16; J24; 330; gender; microeconomic data collection; human capital; work experience; Meinungsforschung; Telefon; Statistische Erhebung; Wissenschaftliche Methode; Datenqualität; Lohndifferenzierung; Geschlecht; USA